2014
DOI: 10.1186/1749-8090-9-74
|View full text |Cite
|
Sign up to set email alerts
|

What is an appropriate material to use with a covering technique to prevent the recurrence of spontaneous pneumothorax?

Abstract: BackgroundThe purpose of this retrospective study was to identify an appropriate material that can be used as a covering for patients with a spontaneous pneumothorax (SP). A total of 279 patients were studied over a period of eight years.MethodsThe patient characteristics, surgical details and perioperative outcomes were analyzed. We compared the clinicopathological characteristics between recurrent and non-recurrent cases, and examined the associations with the material used for covering the SP, such as polyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…Our prospective study followed up patients for 938 ± 496 days and showed that in contrast to the 63.9% of cases with neogenetic bullae at 1 year (404 ± 101 days), only 13.6% of cases developed a recurrence in 869 ± 542 days. These results suggested that additional procedures performed with VATS do not necessarily prevent the development of neogenetic bullae and early phase recurrence, such as recurrence after one month, but they do reduce the rate of rupture of these bullae and postoperative PSP recurrence [1120]. Our results also suggest that the additional procedures likely result in milder postoperative recurrences, as most cases with recurrence were managed conservatively and none required surgical intervention.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Our prospective study followed up patients for 938 ± 496 days and showed that in contrast to the 63.9% of cases with neogenetic bullae at 1 year (404 ± 101 days), only 13.6% of cases developed a recurrence in 869 ± 542 days. These results suggested that additional procedures performed with VATS do not necessarily prevent the development of neogenetic bullae and early phase recurrence, such as recurrence after one month, but they do reduce the rate of rupture of these bullae and postoperative PSP recurrence [1120]. Our results also suggest that the additional procedures likely result in milder postoperative recurrences, as most cases with recurrence were managed conservatively and none required surgical intervention.…”
Section: Discussionmentioning
confidence: 68%
“…The development of neogenetic bullae is thought to be one of the most important causes of postoperative recurrence [510]. In addition to bullectomy using an endoscopic linear stapler, surgical procedures such as partial pulmonary resection, coagulation of the staple lines, coverage of the staple lines and adjacent areas with polyglycolic acid (PGA) sheets and fibrin glue, apical pleural abrasion, and chemical pleurodesis are often performed to prevent the development of neogenetic bullae and the recurrence of pneumothorax [1120].…”
Section: Introductionmentioning
confidence: 99%
“…The first reason is that a PGA patch can decrease the rate of postoperative pulmonary fistula in the pleura. Second, a PGA patch can avoid new bullous formation and inhibit rupture of new bullae [13,23,24]. Our results showed that the incidence of postoperative recurrence is greater in the non-PGA group than in the PGA group; Considering the difference between primary spontaneous pneumothorax and secondary spontaneous pneumothorax, we conducted a subgroup analysis of two spontaneous pneumothoraxes, the results showed that PGA was equally effective in reducing the recurrence of pneumothorax.…”
Section: Discussionmentioning
confidence: 73%
“…Aghajanzadeh et al studied PSP epidemiology in rasht during 2009-2014; in their study, 79.9% of patients were male. The most common clinical symptom (53.2%) was chest pain [9]. Yoon et al examined risk factors for spontaneous pneumothorax in 2013; they showed that 65.7% of patients were male, with the most common complaint being chest pain in 35.2% and shortness of breath in 21.7% [13].…”
Section: Discussionmentioning
confidence: 99%
“…The most common cause of spontaneous pneumothorax is sub pleural bleb apical rupture [8]. PSP is more common in men [9]. Its incidence in men is 7 to 18 cases per 100,000 population per year and in women 1 to 6 cases per 100,000 population per year .…”
Section: Introductionmentioning
confidence: 99%